STUDI MANFAAT YANG DICARI NASABAH UMKM DAN PENGARUHNYA TERHADAP KEPUASAN PADA LAYANAN KREDIT BANK KONVENSIAL - Anissa Sukmaputri; Rr. Iramani (STIE Perbanas Surabaya, 2013)
This research tries to review the factors determining the benefit expected by Micro, Small and Medium enterprise bank customers. It also reviews the effect of benefit expected on satisfaction of credit services given by conventional banks. Besides, this study compares some factors expectedbetween micro, small and medium enterprise bank customers. It is based on theory relationship of relational benefit and satisfaction. With the sample of 150 conventional bank customers of Micro, Small and Medium enterprise in Surabaya and cities surround, analysis is done. This analysis is conducted by descriptive analysis, factor, and multiple regressions using SPSS 18. Relational benefits are expected by micro enterprise is that the customer intimacy to contact personnel, and trust over quality, both factors are influencing satisfaction. For small enterprises, relational benefits expected are that customer intimacy to contact personnel and also conformity of services and priority. From these three factors, factors influencing satisfaction is conformity of services and priority. While for medium enterprises relational benefits expected is customer intimacy to contact personnel, additional services and conformity of services. From these three factors, factors influencing satisfaction is additional services and conformity of services.